Targeting the activated microenvironment with endosialin (CD248)-directed CAR-T cells ablates perivascular cells to impair tumor growth and metastasis - Sarah L Ash; Rebecca Orha; Holly Mole; Meg Dinesh-Kumar; Steven P Lee; Frances K Turrell; Clare M Isacke (Journal for ImmunoTherapy of Cancer)
Background Targeting of solid cancers with chimeric antigen receptor (CAR)-T cells is limited by the lack of suitable tumor-specific antigens and the immunosuppressive, desmoplastic tumor microenvironment that impedes CAR-T cell infiltration, activity and persistence. We hypothesized that targeting the endosialin (CD248) receptor, strongly expressed by tumor-associated pericytes and perivascular cancer-associated fibroblasts, would circumvent these challenges and offer an exciting antigen for CAR-T cell therapy due to the close proximity of target cells to the tumor vasculature, the limited endosialin expression in normal tissues and the lack of phenotype observed in endosialin knockout mice.Methods We generated endosialin-directed E3K CAR-T cells from three immunocompetent mouse strains, BALB/c, FVB/N and C57BL/6. E3K CAR-T cell composition (CD4+/CD8+ ratio), activity in vitro against endosialin+ and endosialin– cells, and expansion and activity in vivo in syngeneic tumor models as well as in tumor-naive healthy and wounded mice and tumor-bearing endosialin knockout mice was assessed.Results E3K CAR-T cells were active in vitro against both mouse and human endosialin+, but not endosialin–, cells. Adoptively transferred E3K CAR-T cells exhibited no activity in endosialin knockout mice, tumor-naive endosialin wildtype mice or in wound healing models, demonstrating an absence of off-target and on-target/off-tumor activity. By contrast, adoptive transfer of E3K CAR-T cells into BALB/c, FVB/N or C57BL/6 mice bearing syngeneic breast or lung cancer lines depleted target cells in the tumor stroma resulting in increased tumor necrosis, reduced tumor growth and a substantial impairment in metastatic outgrowth.Conclusions Together these data highlight endosialin as a viable antigen for CAR-T cell therapy and that targeting stromal cells closely associated with the tumor vasculature avoids CAR-T cells having to navigate the harsh immunosuppressive tumor microenvironment. Further, the ability of E3K CAR-T cells to recognize and target both mouse and human endosialin+ cells makes a humanized and optimized E3K CAR a promising candidate for clinical development applicable to a broad range of solid tumor types.